Oral Precancerous Lesions in Tobacco Users Attending Dental Outdoor in Jhalawar District of Rajasthan - Panwar, Sajid K; Ansari , Shakeel M; Mulla , Shakila K (National Journal of Community Medicine, 2012)
Background: Tobacco is well established risk factor for oral cancer. Different aspects of tobacco consumption like mode of consumption, duration and frequency of consumption might influence occurrence of precancerous lesions. Another factor in tobacco consumption is ‘severity of tobacco use’, which is not assessed routinely while history taking. Precancerous lesion is an alarm for progression towards cancer. Unfortunately awareness regarding precancerous lesion is lacking in the community. Hence the current study was done to correlate different aspects of tobacco consumption with occurrence of precancerous lesion and to know the awareness status of persons having precancerous lesion. Methodology: Cross-sectional study on sample of 240 tobacco users attending dental outdoor. Fagerstrom test for nicotine dependence and smokeless tobacco scale was used to assess severity of nicotine dependence. Results: In the current study prevalence of precancerous lesion was found to be 40%. 73% of subjects were unaware of precancerous lesion. Tobacco dependence severity score >5 (p =0.03) and >5 years duration of consumption (p =0.04) were found significant factors. Conclusion: Severity of tobacco consumption is an important determining factor in precancerous lesion. Intensive community participation is needed for screening precancerous lesions in tobacco users and running awareness program in collaboration with de-addiction services.